Newcastle disease control in Chamwino District, Tanzania: Comparing different methods of vaccine delivery - Wyatt, Amanda; Grace, Delia; Alders, Robyn G.; Bagnol, B.; Young, M.; Msami, H. (International Livestock Research Institute, 2014)
In spite of the availability of Newcastle disease vaccines, uptake by smallholder farmers is generally limited and Newcastle disease remains a major constraint to village poultry keeping in developing countries. This report presents findings from a study on the factors affecting uptake and use of the Newcastle disease vaccine in Chamwino District, Tanzania. Villages where the supply of the vaccine had been supported by the Southern African Newcastle Disease Control Project (SANDCP) five years earlier were compared to villages where the project had not been active. Our results indicate that a supportive vaccine delivery system can encourage Newcastle disease vaccine use and reduce chicken mortality; farmers who had used the vaccine had an average flock size that was 5.5 chickens larger than farmers who had never used the vaccine. Even so, Newcastle disease vaccine demand and uptake would be improved in the study area by increasing the perceived effectiveness, addressing supply chain issues that limited availability, and following a vaccination calendar. Findings from our study suggest that efforts to promote knowledge and awareness of the use and effectiveness of the Newcastle disease vaccine among farmers and those involved in vaccine delivery had been somewhat effectively maintained beyond the end of SANDCP.